Consumer acceptance of second generation GM goods: the case of biofortified cassava in the Northeast of Brazil - González, C.; Johnson, Nancy L.; Qaim, M. (Wiley, 2009)
Biofortified staple foods are currently being developed to reduce problems of micronutrient malnutrition among the poor. This partly involves use of genetic modification. Yet, relatively little is known about consumer acceptance of such second-generation genetically modified (GM) foods in developing countries. Here, we analyse consumer attitudes towards provitamin A GM cassava in the north-east of Brazil. Based on stated preference data, mean willingness to pay is estimated at 60–70% above market prices for traditional cassava. This is higher than the results from similar studies in developed countries, which is plausible given that micronutrient malnutrition is more severe in developing countries. GM foods with enhanced nutritive attributes seem to be well received by poor consumers. However, the results also suggest that acceptance would be still higher if provitamin A were introduced to cassava through conventional breeding. Some policy implications are discussed.